A Greek Thomist : providence in Gennadios Scholarios - Briel, Matthew, 1981- (University of Notre Dame Press, 2020)
"Matthew Briel examines for the first time the appropriation and modification of Thomas Aquinas's understanding of providence by a fifteenth-century Greek Orthodox theologian, Gennadios Scholarios. Briel investigates the intersection of Aquinas's theology, the legacy of Greek patristic and later theological traditions, and the use of Aristotle's philosophy by Latin and Greek Christian thinkers in the thirteenth to fifteenth centuries. The broader aim of the book is to reconsider our current understanding of later Byzantine theology by reconfiguring the construction of what constitutes "orthodoxy" within a pro- or anti-Western paradigm. The fruit of this appropriation of Aquinas enriches extant sources for historical and contemporary assessments of Orthodox theology. Moreover, Scholarios's grafting of Thomas onto the later Greek theological tradition changes the account of grace and freedom in Thomistic moral theology. The particular kind of Thomism that Scholarios develops avoids the later vexing issues in the West of the de auxiliis controversy by replacing the Augustinian theology of grace with the highly developed Greek theological concept of synergy"--